Change and sustainability - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Farming for the future : an introduction to low-external-input and sustainable agriculture by Coen Reijntjes, Bertus Haverkort and Ann Waters-Bayer 1992 250pp ISBN 0 333 57011 1 Pbk produced by ILEIA and published by Macmillan Publishers Ltd 4